Dynamic behaviour of the Marina Bay bridge - Ong, Priscilla See Koon. (2011)
This paper reviews the Stochastic System Identification (SSI) method that has been used to estimate the modal parameters of a vibrating structure, the 280 metre footbridge - Marina Bay Helix Bridge (Singapore) in operational conditions. The ambient vibration measurement is a kind of output data-only dynamic testing where traffics and winds are used as agents responsible for natural or environmental excitation. Therefore an experimental modal analysis procedure for ambient vibration testing will need to base itself on output-only data. Experimental investigations were carried out before the opening of the bridge, and structural responses were recorded. The response data were analyzed using Stochastic Subspace Identification (SSI) algorithm. Frequencies, corresponding mode shapes and damping values were identified to be used for scenario simulation and structural health monitoring. The results have shown that both methods can identify the modal parameters effectively. The quality of the modal estimates were then evaluated and compared. For most modes, the analytical and experimental modal frequencies and mode shapes compare quite well. Based on the findings of this study, Stochastic Subspace Identification (SSI) appears to be capable of capturing much of the complex dynamic behaviour of the bridge with higher accuracy.